Acquisition of wild-type HIV-1 infection in a patient on pre-exposure prophylaxis with high intracellular concentrations of tenofovir diphosphate: a case report. Issue 11 (November 2017) - Hoornenborg, Elske; Prins, Maria; Achterbergh, Roel C A; Woittiez, Lycke R; Cornelissen, Marion; Jurriaans, Suzanne; Kootstra, Neeltje A; Anderson, Peter L; Reiss, Peter; de Vries, Henry J C; Prins, Jan M; de Bree, Godelieve J; et al.
Summary: Background: Pre-exposure prophylaxis (PrEP) with emtricitabine and tenofovir disoproxil fumarate is highly effective against acquisition of HIV infection, and only two cases of infection with a multidrug-resistant virus have been reported under adequate long-term adherence, as evidenced by tenofovir diphosphate concentrations in dried blood spots. We report a case of wild-type HIV-1 infection despite consistent use of emtricitabine and tenofovir disoproxil fumarate. Methods: The patient participated in the Amsterdam PrEP project, a demonstration project of daily and event-driven PrEP. We did extensive testing for HIV, including plasma HIV RNA and nested PCR on bulk peripheral blood mononuclear cells (PBMCs) and sigmoid biopsies after seroconversion. Findings: A 50-year-old man who has sex with men and had been on daily emtricitabine and tenofovir disoproxil fumarate for 8 months presented with fever, urinary tract infection caused by Escherichia coli, anal lymphogranuloma venereum infection, and a positive fourth-generation HIV test. We found an atypical seroconversion pattern, with initially only gp160 antibodies detected in the western blot. HIV RNA could not be detected in plasma, and nested PCR for HIV RNA and DNA on bulk PBMCs and sigmoid biopsies were negative. PrEP was discontinued; 3 weeks later HIV RNA was detected in plasma. No drug-resistant mutations were detected. Tenofovir diphosphate concentrations in dried blood spots were stable and high. Interpretation: To our knowledge, this is the first detailed case report suggesting wild-type HIV-1 infection despite good adherence, evidenced by repeatedly high concentrations of tenofovir diphosphate in dried blood spots. PrEP providers need to be aware that infection can occur despite good adherence. Regular HIV testing and awareness of atypical patterns of seroconversion is highly recommended. Funding: ZonMw, National Institute for Public Health and the Environment, Internal GGD research funds, Aidsfonds, Stichting AmsterdamDiner Foundation, Gilead Sciences, Janssen Pharmaceutica, M A C AIDS Fund, and ViiV Healthcare.